Implementation of inquiry-based field trip method to improve critical thinking and problem solving skills of students on plantae topic - H S Asra; S Diana; A Amprasto (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to analyze the implementation of inquiry-based field trip method in improving the critical thinking and problem solving skills of students on plantae topic. The research method is a pre-experiment, with the research design the one-group pretest-posttest design. The implementation of the study involved 30 students in one of the high schools in Bandung. The research instrument used was observation sheet of the implementation process of inquiry-based field trip method, critical thinking and problem solving skills test instrument, student response questionnaire. Data were analyzed using Microsoft Excel program. The results of the implementation show that inquiry-based field trip method contributes in improving the critical thinking and problem solving skills. The result showed that there was a difference in the scores of the pretest and the posttest of critical thinking and problem solving skills of students. The average N-gain for critical thinking skills included medium category, and for problem solving skills included high category. The average percentage of the implementation process of inquiry-based field trip method included very good category, and the students gave very good responses to the implementation of inquiry-based field trip method.